2012
DOI: 10.1093/ije/dys167
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: The International Collaboration of Incident HIV and Hepatitis C in Injecting Cohorts (InC3) Study

Abstract: The International Collaboration of Incident HIV and Hepatitis C in Injecting Cohorts (InC(3)) Study is an international multi-cohort project of pooled biological and behavioural data from nine prospective cohorts of people who inject drugs (PWID). InC(3) brings together researchers from Australia, Canada, USA and the Netherlands with expertise in epidemiology, biostatistics, clinical and behavioural sciences, virology and immunology to investigate research questions relevant to hepatitis C virus (HCV) and HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 32 publications
2
71
0
Order By: Relevance
“…Study Subjects. HCV acutely infected subjects were recruited among high-risk HCV-seronegative injection drug users participating in the Montreal Hepatitis C Cohort at the Saint-Luc Hospital of the University of Montreal Health Center as previously described (44). Blood samples were processed and analyzed as previously described (45).…”
Section: Methodsmentioning
confidence: 99%
“…Study Subjects. HCV acutely infected subjects were recruited among high-risk HCV-seronegative injection drug users participating in the Montreal Hepatitis C Cohort at the Saint-Luc Hospital of the University of Montreal Health Center as previously described (44). Blood samples were processed and analyzed as previously described (45).…”
Section: Methodsmentioning
confidence: 99%
“…The InC 3 study has been described previously [14]. All cohorts followed up participants at regular intervals, using standardized methods (Table 1).…”
Section: Study Population and Designmentioning
confidence: 99%
“…The International Collaboration of Incident HIV and HCV in Injecting Cohorts (InC 3 ) study, which pooled data from 9 prospective cohorts in Australia, Canada, the Netherlands, and the United States [14], mainly comprising from people who inject drugs, enables assessment of HCV reinfection in well-characterized HCVinfected participants. The aims of our study were to characterize the natural history of spontaneous clearance following primary infection ( primary clearance), HCV reinfection, and spontaneous clearance following reinfection (reclearance) in the InC 3 study; assess differences in peak HCV RNA levels during reinfection, compared with primary infection; assess predictors of HCV reclearance; and assess differences in the time to primary clearance and reclearance.…”
mentioning
confidence: 99%
“…The contributions to this repository came from 9 prospective cohorts constituting the International Collaboration of Incident HIV and Hepatitis C in Injecting Cohorts (InC3) [11]. Phylogenetic analysis of these sequences has shown that North American and Australian sequences clustered separately from each other, suggesting that HCV largely evolves separately in microepidemics in geographically separate communities [10].…”
mentioning
confidence: 99%